OC14.05: Impact of fetal endoscopic tracheal occlusion on postnatal outcome according to the severity of congenital diaphragmatic hernia - Rodrigo Ruano; N. Sananès; I.S. Britto; Joan Mastrobattista; Maria Paula Grossi Queiroz Silva; Uenis Tannuri; Marcelo Zugaib (2015)
To evaluate the impact of fetal endoscopic tracheal occlusion (FETO) on the postnatal outcome in fetuses with congenital diaphragmatic hernia (CDH) according to the severity of the disease. Between January 2004 and December 2011, a total of 152 fetuses with isolated CDH were evaluated in a single center; 42 patients with severe CDH underwent FETO from 24 to 30 weeks while 108 did not have fetal intervention. Prenatally, CDH was classified as severe (LHR < 1.0 and 1/3 of liver herniation), moderate (LHR ≥ 1.0 and < 1.4 and 1/3 of liver herniation) and mild (LHR > 1.4). Outcomes included postnatal survival at 6 months of age and postnatal diagnosis of severe pulmonary arterial hypertension (PPH). The survival rate was 54.8% (23/42) in the FETO group vs. 35.2% (38/108) in the non-fetal intervention group (p = 0.03). Severe PPH was diagnosed in 47.6% (20/42) in the FETO group vs. 63.0% (68/108) in the non-fetal intervention group (p = 0.10). Among infants that did not undergo fetal intervention, postnatal survival was 5.9% (3/51), 44.7% (17/38) and 94.7% (18/19) in severe, moderate and mild CDH, respectively (p < 0.01), while postnatal survival in the FETO group was 54.8% (23/42). Among infants that did not undergo fetal intervention, severe PPH was diagnosed in 90.2% (46/51), 50.0% (19/38) and 15.8% (3/19) in severe, moderate and mild CDH, respectively (p < 0.01), while severe PPH was 47.6% (20/42) in the FETO group. FETO improves postnatal outcomes in infants with severe CDH to a less severe form of the disease comparable to infants with moderate CDH who did not undergo fetal intervention. Our results suggest that FETO improves one ‘category' (from severe to moderate), which supports the hypothesis that FETO may improve postnatal outcomes from an initial moderate condition to a mild form of the disease.